Transcriptome and DNA Methylome Reveal Insights Into Phytoplasma Infection Responses in Mulberry (Morus multicaulis Perr.) - Liu, Chaorui; Dong, Xiaonan; Xu, Yuqi; Dong, Qing; Wang, Yuqi; Gai, Yingping; Ji, Xianling (Frontiers in Plant Science, 2021)
To reveal whether the response of mulberry to phytoplasma infection is associated with genome-wide DNA methylation changes, the methylome and transcriptome patterns of mulberry in response to phytoplasma infection were explored. Though the average methylation level of infected leaves showed no significant difference with that of healthy leaves, there were 1253 differentially methylated genes and 1168 differentially expressed genes in the infected leaves, and 51 genes were found simultaneously to be differently methylated and expressed. It was found that the expression of G-type lectin S-receptor-like serine/threonine protein kinase gene (Mu-GsSRK) was increased, but its methylation level was decreased in the pathogen infected or salicylic acid treated leaves. Overexpression of Mu-GsSRK in Arabidopsis and hairy roots of mulberry enhanced transgenic plant resistance to the phytoplasma. Moreover, overexpressing Mu-GsSRK enhanced the expressions of pathogenesis-related protein 1, plant defensin and cytochrome P450 protein CYP82C2 genes in transgenic plants inoculated with pathogens, which may contribute to the enhanced disease resistance against various pathogens. Finally, the DNA methylation dynamic patterns and functions of the differentially expressed and methylated genes were discussed. The results suggested that DNA methylation has important roles in mulberry responses to phytoplasma infection.